Downregulation of inflammatory markers by conjugated linoleic acid isomers in human cultured astrocytes. (4th March 2019) - Saba, Francesca; Sirigu, Annarita; Pillai, Rita; Caria, Paola; Cordeddu, Lina; Carta, Gianfranca; Murru, Elisabetta; Sogos, Valeria; Banni, Sebastiano
Abstract : Objectives: Conjugated linoleic acid (CLA) isomers have been shown to possess anti-inflammatory activity in the central nervous system. In this study, we aimed to evaluate whether modulation of the fatty acid profile by the CLA isomers c9, t11 or t10, c12CLA was associated with changes in the expression of pro-inflammatory molecules in human astrocytes. Methods: Cultured astrocytes were treated for 6 days with 100 µM fatty acids (c9, t11CLA or t10, c12CLA or oleic acid). Following the treatment, the fatty acid profile of the cell and pro-inflammatory molecule expression were assessed. Results: Only the t10, c12CLA isomer induced a significant decrease in arachidonic acid and increased the ratio of docosahexaenoic acid/eicosapentaenoic acid, which constitutes indirect evidence of peroxisome proliferator-activated receptor alpha activation. Inhibition of tumour necrosis factor-α, interleukin-1β, and RANTES expression was observed in astrocytes treated with c9, t11CLA and t10, c12CLA. Discussion: Current data demonstrate that CLA isomers, particularly t10, c12, may affect neuroinflammation by reducing the pro-inflammatory molecules in cultured astrocytes, suggesting a potential nutritional role of CLA isomers in modulating the astrocyte inflammatory response.